Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2015
DOI: 10.1097/bpo.0000000000000253
|View full text |Cite
|
Sign up to set email alerts
|

Pediatric Proximal Phalanx Fractures

Abstract: Background The outcomes literature on proximal phalanx fractures in children is sparse. The purpose of this study is to report the complications and outcomes of displaced proximal phalanx fractures after treatment with closed reduction and percutaneous pinning. Methods A retrospective chart review identified 105 patients treated with closed reduction and percutaneous pinning of displaced proximal phalanx fractures. Specific complications were recorded for all patients. Thirty-one of these patients returned m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(9 citation statements)
references
References 14 publications
(12 reference statements)
0
8
0
Order By: Relevance
“…The preoperative clinical and radiographic data of the two groups of patients were comparable, and it is possible that multiple attempts to percutaneously fix such injuries, may have contributed to higher rate of malunion and pain (iatrogenic) in patients treated surgically. Boyer et al [8] also found that pediatric patients (n = 105) with displaced FBPP managed by percutaneous pinning have a notable complication rate related to the stiffness. In this study, we also found one patient had malunion and developed mild pain following CRPP.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…The preoperative clinical and radiographic data of the two groups of patients were comparable, and it is possible that multiple attempts to percutaneously fix such injuries, may have contributed to higher rate of malunion and pain (iatrogenic) in patients treated surgically. Boyer et al [8] also found that pediatric patients (n = 105) with displaced FBPP managed by percutaneous pinning have a notable complication rate related to the stiffness. In this study, we also found one patient had malunion and developed mild pain following CRPP.…”
Section: Discussionmentioning
confidence: 96%
“…Treatment of FBPP in children remains debated. Following closed reduction, some authors recommend the use of Kirschner wires (K-wires) to restore the finger’s maximal range of motion (ROM) and maintain reduction [8,9], while others report that cast immobilization may be enough because of the significant remodeling potential in children [1,3,10].…”
Section: Introductionmentioning
confidence: 99%
“…Many researchers believe that phalangeal fractures in children have strong bone shaping ability and do not require anatomical reduction. In clinical practice, it is not rare for patients with inaccurate fracture fixation and fracture displacement to obtain conservative treatment (11,(13)(14)(15)(16)(17). The phalangeal head in children is primarily cartilaginous and has no tendon attachments.…”
Section: Discussionmentioning
confidence: 99%
“…The phalangeal head in children is primarily cartilaginous and has no tendon attachments. Once the fracture of the phalanges neck is displaced or rotated, it will eventually lead to malunion, often causing finger deformity and joint rigidity, and affecting function (13)(14)(15)18). Therefore, for children whose fingers are angulated, rotated, limited in function, unable to cooperate, and have poor compliance, more doctors are recommending the use of internal fixation (11,19).…”
Section: Discussionmentioning
confidence: 99%
“…Management of isolated proximal phalangeal neck fractures is controversial with few studies suggesting Closed reduction and pinning [ 9 ] with most requiring formal hand physiotherapy. Similar outcomes between non-operative and operative methods of fixation [ 10 ] have been suggested, when dorsal extension block splinting has been elected as a definitive treatment for these injuries.…”
Section: Discussionmentioning
confidence: 99%